MENINGKATKAN HASIL BELAJAR MATA PELAJARAN EKONOMI MELALUI PERPADUAN METODE CERAMAH DAN METODE TWO STAY TWO STRAY PADA KELAS X AP SMK HIDAYAH SEMARANG - Listianah, Dian (Economic Education Analysis Journal, 2013)
The purpose of this research is to improve student learning outcomes SMK Hidayah Semarang on the material types of economies and enhance students' learning activities in the classroom with a mix of lecture method and the method of Two Stay Two Stray. Data collection method is the method of the test (with multiple choice) and non-test method (observation and documentation). The results of this study were obtained percentage of students in the learning activities of the first cycle with both categories (70%) and the second cycle increases with the category very well (87.5%). The percentage of all teachers in the first cycle of learning that is with either category (66.6%) and the second cycle increases with the category very well (90.2%). The average grade achieved in the first cycle is 71.81 with the achievement of the classical completeness by 75% and in the second cycle class average increased to 80.23 and the achievement of the classical completeness of 91.6%. From the results of this study concluded that learning in the classroom with a mix of lecture method and the method of Two Stay Two Stray able to improve student learning outcomes and student activities.